Experimental investigation characteristics of palm biodiesel blends on the combustion diethyl ether - Doresharan, Gangatharan (2021)
Depletion of fossil fuel and particularly environmental pollution done by diesel fuel has driven an initiative to resource for an alternative fuel for diesel engines. Diesel fuel pollutes the environment by emitting carbon mon oxide (CO), nitrogen oxide (NOx), particulate matter (PM) as well as unburnt hydrocarbons. This particularly degrades the environment as well possess threat to human health. This research focuses on biodiesel B7 combined with diethyl ether with specific pe of 5%, 7% and rcentage 9% respectively. A combustion chamber was built to analyse the characteristic of a single fuel droplet. High speed video was taken to analyse the ignition delay, burning duration and micro explosion. The burning of diethyl ether blen ds with palm biodiesel has shown a constant rate, which indicates higher oxygen molecules allows for a clean combustion. Micro explosion also was seen as soon as the percentage of diethyl ether was added, which increases evaporation rate and improved the c ombustion properties of palm biodiesel.